Review of the Plant Jalapippali (Phyla Nodiflora) - An Under Exposed Plant (International Journal of Ayurveda and Pharma Research, 2023)
Ayurved provide a strong base for utilization of a large number of plants in general healthcare as well as alleviation of diseases. Jalapippali which is identified as Phyla nodiflora L. Greene syn Lyppa nodiflora, family Verbinaceae, is found in most of the states throughout India at riverbanks, along lakes and near fresh water bodies. Jalapippali has been explained in most of the Nighantus in Ayurved. Aim: the study aims to review the under exposed plant Jalapippali from available classical texts and modern sources to highlight its therapeutical importance. Methods: The study covers to summarize the literature in the available Ayurved classical texts while identifying the potential areas for further development of this herb for therapeutical uses in the field of Ayurveda. Result: Even though very fewer references are available in Ayurved-Brihatrayee, but during the Nighantu period most of the Nighantus have highlighted its therapeutical importance. The references are available even in the oldest Nighantu- Dhanwantatari, and many researchers suggest, the plant is rich in many important medicinal useful compounds. And the plant contains a variety of constituents such as triterpenoids, flavonoids, phenols, steroids, etc. The plant is having significant antimicrobial, anti-inflammatory, antidiuretic etc. activities. Conclusion: Jalapippali is one of the important plants. Especially the Nighantus have highlighted its importance. The recent studies suggest its pharmacological values. Hence further clinical studies should be carried out for its therapeutical values. And also, the Jalapippali mentioned in Brihatrayees has to be explored for its botanical identification so as to redefine its clinical importance.